Ultrastructure of Thyrocytes in Young Rats at Neurogenic Arterial Hypertension and Following Administration of Cryopreserved Cord Blood Nucleated Cells - Babiychuk, Lyudmila V.; Nevzorov, Vyacheslav P.; Nevzorova, Olga F.; Babiychuk, Vladislav G. (Problems of Cryobiology and Cryomedicine, 2013)
In order to justify the expediency of application of cord blood preparations in therapy of neurogenic stress-induced arterial hypertension we carried out an electron-microscopic study of changes in ultrastructure of thyrocyte organelles in young rats with arterial hypertension prior to and after introduction of cryopreserved cord blood nucleated cells. The study of submicroscopic organization of thyrocytes demonstrated the presence of dystrophic changes in organelles, manifestation degree of which varied depending on the pathology development term. Submicroscopic architecture of thyrocytes in rats with stress-induced neurogenic arterial hypertension was established as acquired the normal structure one month later introduction of cryopreserved preparation of cord blood nucleated cells.Probl Cryobiol Cryomed 2013; 23(4):309–317.